International Monetary Fund Annual Report 1952. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1952)
This paper reviews key findings of the IMF's Annual Report for the fiscal year 1952. The report highlights that five years since the IMF began operations, there has been a remarkable growth in production and one widespread adjustment of exchange rates. The attainment of a stable international equilibrium, however, still eludes large parts of the world, and there has been little secure or sustained progress toward the IMF objectives of unimpeded multilateral trade and the general convertibility of currencies. The report also discusses the use of the IMF's resources, gold policy, and exchange restrictions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet